Children Confidence Development by Theme Based Movement and Singing Method at RA Islamic Tunas Bangsa 4 Ngaliyan Semarang - Lestari, Rizqy Kusuma; Handayani, Sri Sularti Dewanti (BELIA: Early Childhood Education Papers, 2017)
Confidence is one of important thing that should be developed from the early years. Having a confidence, encourages us to deal with a risk in the future. The important key about having a confidence in an early years is because the children will be able to finish their task according to development phase, having such a courage to take a risk and get their achievement, trusted by people, growing up in the middle of experienced life, and the most important is, the children will be healthy and become independent.  To develop childrenâs confidence, singing method by theme based movement can be used. The themes used to apply this method are children themselves, animal and plants.  The method used in this research was Pre Experimental with One Group Pretest-Posttest. The populations of this research were all of the kindergarten students in Ngaliyan and the sample were 30 students of RA Islamic Tunas Bangsa 4. Purposive sampling was used to take the data sample. There were two variables in this study, X was a singing method with theme based movement and Y was childrenâs confidence. The result of the study showed that the measurement of Paired t-test, between pretest and posttest from the experimental group was tvalue = -12,636 with sig value (2-tailed)< 0,05. Therefore, from hypothesis test we could accept H0 and refused Ha. Before conducting the treatment the mean of pretest score was 7,53 and after the treatment, the posttest score was 12,17. From the result of the mean of posttest improvement; 4,64, and it can be said that the childrenâs confidence was developed. The conclusion of this study was childrenâs confidence at RA Islamic Tunas Bangsa 4 Ngaliyan can be developed by this method.